Exposure to authoritarian values leads to lower positive affect, higher negative affect, and higher meaning in life. - Jake Womick (Public Library of Science (PLoS), 2021)
Five studies tested the effect of exposure to authoritarian values on positive affect (PA), negative affect (NA), and meaning in life (MIL). Study 1 (N = 1,053) showed that simply completing a measure of right-wing authoritarianism (vs. not) prior to rating MIL led to higher MIL. Preregistered Study 2 (N = 1,904) showed that reading speeches by real-world authoritarians (e.g., Adolf Hitler) led to lower PA, higher NA, and higher MIL than a control passage. In preregistered Studies 3 (N = 1,573) and 4 (N = 1,512), Americans read authoritarian, egalitarian, or control messages and rated mood, MIL, and evaluated the passages. Both studies showed that egalitarian messages led to better mood and authoritarian messages led to higher MIL. Study 5 (N = 148) directly replicated these results with Canadians. Aggregating across studies (N = 3,401), moderational analyses showed that meaning in life, post manipulation, was associated with more favorable evaluations of the authoritarian passage. In addition, PA was a stronger predictor of MIL in the egalitarian and control conditions than in the authoritarian condition. Further results showed no evidence that negative mood (or disagreement) spurred the boost in MIL. Implications and future directions are discussed.